Congenital and developmental buccal alterations in infants 0 to 12 months of Instituto Nacional de Salud del Niño - Marcos-Pari, Jean (2014)
The objective of the study was to determine the frecuency of congenital and developmental oral alterations in infants aged 0 to 12 months, of Instituto Nacional de Salud del Niño since July to December 2008. Methodology: prior informed consent of the parents, stomatological examination in 109 infants, 56 male and 53 female, was performed. Instrumental was used in clinical examinations, artificial light source of dental unit and a data collection sheet. Results and conclusions: 72,5% of the totality examined infant, showed congenital and developmental oral alterations. The prevalent ones were the Böhn’s nodules with 40,3%, the persistent upper labial frenulum with 30,2% and the Epstein’s pearls with 29,3% of cases. No significant differences with respect to gender and age group were found. From the group that presented oral congenital and developmental abnormalities, 45.9% were born at term and in 29.4% no need for treatment. The more committed anatomical structures were the alveolar processes 65.1% of cases. We concluded that oral congenital and developmental abnormalities are highly prevalent in this age group. Therefore it is important for dentists to have a vast knowledge of these, in order to make an early diagnosis, early treatment and regular monitoring of its evolution.